2004
DOI: 10.1152/ajpendo.00088.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol rapidly suppresses intracellular calcium and voltage-gated calcium channel activity in prolactin cells of the tilapia (Oreochromis mossambicus)

Abstract: . Cortisol rapidly suppresses intracellular calcium and voltage-gated calcium channel activity in prolactin cells of the tilapia (Oreochromis mossambicus). Am J Physiol Endocrinol Metab

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…Corticosteroids may also exert rapid and/or non-genomic effects on ion transport (see Sakamoto et al (2001) and McCormick & Bradshaw (2006)) as has been demonstrated for aldosterone on ion regulation in tetrapods (see Harvey et al (2002)). In fish, rapid effects of glucocorticoids have been reported with regard to inhibition of pituitary prolactin release in tilapia (Borski et al 2001, Hyde et al 2004, lipogenic enzyme activity in tilapia liver cells (Sunny et al 2002) and on Na C ,K C -ATPase activity in the eel and tilapia gill (Marsigliante et al 2000, Sunny & Oommen 2001. We demonstrate in this study that both cortisol and DOC may rapidly affect (within 30 min) the MAPK signalling cascade via an increase in the phosphorylation state of ERK1 and ERK2.…”
Section: Rapid Effects Of Corticosteroidssupporting
confidence: 55%
“…Corticosteroids may also exert rapid and/or non-genomic effects on ion transport (see Sakamoto et al (2001) and McCormick & Bradshaw (2006)) as has been demonstrated for aldosterone on ion regulation in tetrapods (see Harvey et al (2002)). In fish, rapid effects of glucocorticoids have been reported with regard to inhibition of pituitary prolactin release in tilapia (Borski et al 2001, Hyde et al 2004, lipogenic enzyme activity in tilapia liver cells (Sunny et al 2002) and on Na C ,K C -ATPase activity in the eel and tilapia gill (Marsigliante et al 2000, Sunny & Oommen 2001. We demonstrate in this study that both cortisol and DOC may rapidly affect (within 30 min) the MAPK signalling cascade via an increase in the phosphorylation state of ERK1 and ERK2.…”
Section: Rapid Effects Of Corticosteroidssupporting
confidence: 55%
“…A rapid action of glucocorticoids on Leydig cell function was also demonstrated. A rapid (30-min) decline of testosterone production was seen in mouse Leydig cells when these cells were exposed to 1.44 µM corticosterone (CORT), indicating that a non-genomic mechanism of glucocorticoids in Leydig cells [28], since the genomic mechanism of glucocorticoids requires hours to register at the protein level [29]. CORT can inhibit cAMP formation in mouse Leydig cells within 15 min [28].…”
Section: Rapid Glucocorticoid Actions Via Membrane Receptorsmentioning
confidence: 99%
“…While the most rapid genomic effect reported for glucocorticoids takes little more than 7 minutes, such as in the case of the glucocorticoid-induced transcription of the mouse mammary tumor virus long terminal repeat in L tk2 aprt2 cells (Groner et al, 1983), genomic glucocorticoid actions usually require more than an hour before they are detectable (Joels and De Kloet, 1992). Non-genomic effects of glucocorticoids, on the other hand, occur more rapidly, often taking only seconds to minutes to be detected (Ffrench-Mullen, 1995;Hyde et al, 2004;Malcher-Lopes et al, 2006). The non-genomic actions of glucocorticoids may involve multiple mechanisms mediated by intracellular and/or membrane-associated receptors.…”
Section: Introductionmentioning
confidence: 99%